Toward Effective Electoral Affairs: The Implementation of E-Voting in the Village Chief Executive Election 2021 - Fairuz Arta Abhipraya; Bagaskoro Nur Abu Yogar; Satria Iman Prasetyo (Universitas Pancasakti Tegal, 2023)
The purpose of this study is to determine the effectiveness of the election of Village Chief Executive in Sleman regency in the Special Region of Yogyakarta. Where at first it was implemented traditionally or conventionally which later changed to use the e-voting system. The method used in this study is a qualitative type. The data used is data obtained from previous research (books, journals, and articles). To measure the effectiveness of e-voting, researchers use Duncan's theory of effectiveness, where this theory has three indicators, namely: 1) Goals of Achievement, 2) Integration, and 3) Adaptation. The results of this study are: 1) the Sleman community gets convenience in using or executing e-voting when conducting digital elections, which is shown with a percentage of 50.00%. This is supported by the increase in voting rights from 2020 to 2021. Then, 2) the intensified socialization is a form of direct socialization, because it is considered more effective, it can be seen with a percentage of 61.00%. And the last one is 3) the people of Sleman can adapt from conventional elections to a digital system, namely e-voting. The Sleman regency government also collaborated with seven universities in Indonesia to make the election of village heads successful by e-voting.